Strong Manual Acupuncture Manipulation Could Better Inhibit Spike Frequency of the Dorsal Horn Neurons in Rats with Acute Visceral Nociception. (15th July 2015) - Hong, Shouhai; Ding, Shasha; Wu, Fei; Xi, Qiang; Li, Qiang; Liu, Yangyang; Zhou, Tao; Qing, Cai; Guo, Yongming; Guo, Yi
Abstract : Afferent impulses from visceral nociception can be regulated by acupuncture at spinal cord level; however, the effects of different manual acupuncture (MA) manipulations on the afferent impulses are still unknown. Here, we analyzed the spike frequency of excitatory gastric-related wide dynamic range (WDR) neurons in spinal dorsal horn (SDH) following acute gastric distension (GD) in rats and compared their responses to MA manipulations with four different frequencies (0.5, 1, 2, and 3 Hz) at Zusanli (ST36). Results indicated that the spike frequency was increased by acute GD stimulation. Under acute GD circumstances, the spike frequency was further activated by weak MA stimulation (0.5 and 1 Hz), while being significantly inhibited by strong MA stimulation (2 and 3 Hz). After 10 minutes of the strong MA stimulation, same intensity of acute GD caused less spike frequency. Our previous researches had demonstrated that different MA manipulations could increase spike frequency in an intensity-dependent manner in normal rats; these findings suggest that acupuncture may have different modulatory effects depending on the state of the stomach. Since neuronal spike frequency was related to the level of nociception, the results suggest that strong MA manipulation may have better effect on acute visceral nociception.